Association of the MACROD2 rs6110695 A>G polymorphism with an increasing WBC count in a Korean population. Issue 7 (25th June 2022) - Yang, Jihye; Han, Youngmin; Lee, Jong Ho; Yoo, Hye Jin
Abstract: Introduction: We aimed to find a novel candidate gene related to the white blood cell (WBC) count in a Korean population. Since WBC count has been reported to have a relation to the risk of chronic diseases according to previous literature, WBC level prediction can be helpful for managing future risk of chronic disease development. In this aspect, a gene newly found in the present study is expected to be utilized as a tool for judging an individual's WBC level. Methods: Based on the 153 study participants' genotype data produced by the Korean Chip. The mono‐adenosine diphosphate ribosylhydrolase 2 ( MACROD2 ) rs6110695 A>G polymorphism had a significant strong association with WBC count, thus, the MACROD2 gene emerged as a novel candidate gene for WBC count. To verify the effects of the single‐nucleotide polymorphisms on WBC count, the participants were grouped according to the rs6110695 AA and AG genotypes. Results: WBC to apolipoprotein A‐I ratio, WBC count, granulocyte to lymphocyte ratio, monocyte to platelet ratio, and interferon‐ γ level were significantly higher in the AG genotype group than in the AA genotype group. Through the receiver operating characteristic curve analysis, the rs6110695 AA and AG genotypes were discriminated by the optimal WBC count cutoff value of 5.450. As expected, the results in the participants having a WBC count over 5.450 were similar to the AG genotype group. Conclusions: We revealed that the MACROD2 rs6110695 AG genotype has an association with increasing WBC count. Since, as previous literature described, WBC count is one of the main risk factors for chronic diseases, WBC count measurement in individuals with the rs6110695 AG genotype that was found in the present study may help manage future chronic disease risk. Abstract : We revealed the MACROD2 rs6110695 AG genotype has an association with increasing white blood cell (WBC) count, which is one of the risk factors for chronic disease in a Korean population. WBC count measurement in individuals with the rs6110695 AG genotype may help manage the future risk of developing chronic disease.